A robust power control scheme for femtocell networks with probability constraint of channel gains - Liu, Z.; Li, S.; Guan, X.; Chan, Kit Yan (2016)
In this paper, a robust power control algorithm is proposed in two-tier femtocell network system in order to address the uncertain channel gains of the interference links. In the algorithm, an outage probability is used to guarantee the communication qualities of users. As the deterministic form of the outage probability constraint is not convex of power, a novel and simple method is utilized to solve the power allocation problem. The allocation solution can be determined based on the average channel gains which are engaged with a dynamic factor with average signal-to-interference-plus-noise ratio. In the scheme, a dynamic power adjustment algorithm is developed. The algorithm attempts to guarantee the outage probability requirement of the macrocell user, and to achieve the optimal power allocation of femtocell users. Apart from the appropriate resource for the network, an admission control algorithm is adopted to remove the femtocell user whose communication quality can not be ensured. Numerical results demonstrate the effectiveness of the robust power control algorithm and also explain the admission control algorithm.